2018
DOI: 10.1016/j.msea.2018.04.036
|View full text |Cite
|
Sign up to set email alerts
|

A synchrotron X-ray and electron backscatter diffraction based investigation on deformation and failure micro-mechanisms of monotonic and cyclic loading in titanium

Abstract: Synchrotron X-ray diffraction technique has been used to estimate defect structure in terms of dislocation density, crystallite size and micro-strain in commercially pure titanium subjected to tension and cyclic deformation in stress and strain control mode. Statistical analysis of microtexture data collected from electron backscatter diffraction approximately from the same region as that of synchrotron X-ray has been used to correlate orientation dependent micro-strain and dislocation density with deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Contraction twins require higher stress to nucleate and hence of dislocation pile ups are the potential nucleation site for contraction twins [13]. However, the amount of stored dislocation density in tensile specimen is much higher compared to ratcheting specimen [24]. This is due to the formation of dislocation pile up and tangles during tensile deformation while stable dislocation configuration like well organized dislocation cell structure forms during cyclic deformation.…”
Section: Orientation Specific Damage Evolution During Fatiguementioning
confidence: 99%
“…Contraction twins require higher stress to nucleate and hence of dislocation pile ups are the potential nucleation site for contraction twins [13]. However, the amount of stored dislocation density in tensile specimen is much higher compared to ratcheting specimen [24]. This is due to the formation of dislocation pile up and tangles during tensile deformation while stable dislocation configuration like well organized dislocation cell structure forms during cyclic deformation.…”
Section: Orientation Specific Damage Evolution During Fatiguementioning
confidence: 99%
“…The aforementioned background necessitates the study of α → ω transformation in Ti from a microstructural standpoint to elucidate the underlying deformation micromechanisms. In line with this, we investigated the initial texture and microstructure dependence of tensile and cyclic deformation behavior of commercially pure titanium (cp-Ti) in our previous studies [18][19][20][21][22]. The initial orientation of specimens were described with respect to sample rolling, transverse and normal directions (RD, TD and ND, respectively), considering both in-plane specimens from the RD-TD plane and out-of-plane specimens from the ND-RD and ND-TD planes.…”
Section: Introductionmentioning
confidence: 97%
“…Yin et al [7] have shown the detwinning phenomenon during load reversal of Mg responsible for the asymmetry in the hysteresis loop where yield stress in compression is lower than yield stress in tension. The deformation micro-mechanism of CP-Ti involves complex dislocation-dislocation interaction and dislocation/twin boundary interaction and is highly orientation-specific [8]. Hence, it is expected that the initial grain orientation will have a strong influence on load reversal deformation behaviour.…”
Section: Introductionmentioning
confidence: 99%